The Association Between The Physical Condition of the House and the Smoking Habits of Residents with the Incidence of Pneumonia In Children Under Five Years - Desy Mery Dorsanti; Nurjazuli Nurjazuli; Mursid Raharjo (Jurnal Penelitian Pendidikan IPA, 2024)
Pneumonia is leading cause of death worldwide, with a prevalence of 44%, and is second leading cause of death among under-fives in Indonesia, at 15.5%. Pneumonia is caused by viruses and bacteria that are associated with physical conditions, air quality, and smoking habits in house. This study aimed to determine association between physical house conditions and smoking habits with incidence of pneumonia in children under five years in Cengkareng Health Center working area. This study was a case-control design analytic observational study. Population involved chindren under five aged 12-59 months with a sample of 43 cases and 43 controls calculated using Lemeshow’s formula, taken using purposive sampling technique. Independent variables included floor and wall types, ventilation, occupancy density, temperature, humidity, light intensity, PM10 and PM2.5 levels, and smoking habits. Dependent varariable are incident of pneumonia. Data were collected through observation, sanitarian kits, and questionnaires. Data were analyzed using chi-square and logistic regression with 95% CI and alpha 0.05. The results showed that PM2.5 levels (p=0.010, OR=3.290, 95% CI=1.323-8.181) and indoor smoking (p=0.044, OR=2.758, 95% CI=1.027-7.410) were most significant factors associated with pneumonia. This study recommends optimizing educational programs regarding PM2.5 exposure and smoking habits to improve healthy living practices and reduce risk of pneumonia